The rite and common language — the Sacrament of Reconciliation as a dialogue - Sitkowska, Katarzyna (Name – style – text: A jubilee book dedicated to Professor Elżebieta Umińska-Tytoń, 2023)
This paper presents the Sacrament of Reconciliation as a dialogue in a specific sender-receiver relationship. The expressions included in the Rite of Penance as well as the confession of sins are shown as dialogic. It recommends paraphrasing while in a conversation with a penitent as it can help him or her celebrate the sacrament in a deeper way.